Trends in the lung cancer incidence and mortality in the Slovak and Czech Republics in the contexts of an international comparison - Ondrusova, Martina; Muzik, Jan; Hunakova, Lubica; Belohorska, Bela; Tomek, Dominik; Ondrus, Dalibor; Kavcova, Elena (Clinical & translational oncology, 2012)
INTRODUCTION: Lung cancer represents the most frequent cause of cancer-related deaths in the industrialized countries. The aim of this study was to analyze the lung cancer incidence and mortality and the possible reasons for any differences discovered in two neighboring Central European countries-the Slovak Republic. METHODS: We used linear regression model when analyzing incidence and mortality; the trends are presented with corresponding 95% confidence intervals (CI) and p-value with null hypothesis being constant with time. RESULTS: Statistically significant increase of age-standardized incidence (0.707/100,000/year, 95% CI 0.107-1.307, p = 0,025) and mortality (1.339/100,000/year, 95% CI 1.050-1.629, p < 0.0001) of the lung cancer was revealed in males in the Slovak Republic (1980-1991). On the contrary, values of both indicators were stabilized in the Czech Republic. Since year 1991-2005 a statistically highly significant decrease of both incidence and mortality values was observed in males, which was greater in the Slovak Republic. Peak of the curve was not reached in women population, while incidence and mortality values have significantly continuous growth in both countries. CONCLUSIONS: According to the lung cancer incidence and mortality trends in both countries (in correlation with smoking prevalence) we consider the support of efforts to change the attitude towards smoking predominantly in women and younger generation to be the most accurate action to reduce these trends.
Keywords: Linear Models; Česká republika; Smoking; Czech Republic; Incidence; Male; Slovakia; lidé; Female; nádory plic; ženské pohlaví; lineární modely; incidence; mužské pohlaví; Slovenská republika; kouření; Humans; Lung Neoplasms